The ardent pilgrim : an introduction to the life and work of Mohammed Iqbal - Singh, Iqbal, 1912- (Oxford University Press, 1997)
Mohammed Iqbal, one of the pre-eminent Urdu and Persian poets of our time, had described himself in one of his couplets as a sum of contradictions. This book is an attempt at understanding the contradictions that made him legendary as a poet and valorized as a prophet of pan-Islamic ideas. Iqbal Singh investigates the poet's personality through a study of his poetry, while situating him within his political and social context. In doing so, the author vividly depicts pre-Partition India, as well as the character of the Muslim intelligentsia and its dilemmas at the time. Originally published in 1951, this biography has now been thoroughly revised with the help of a great deal of biographical material that has been unearthed since. The author has added a chapter which explores Iqbal's personal life, including his relations with his three wives and his alienation from his elder son. In this sympathetic yet balanced account, the great poet emerges a complex, fallible man.